Efficacy of neem leaf meal as a hypocholesterolemic dietary additive in laying pullets (Bangladesh Journal of Animal Science, 2012)
An experiment was carried out with laying pullets to investigate the effects of feeding neem (Azadirachta indica) leaf meal (NLM) at different dietary concentrations on cholesterol metabolism and productivity of laying chickens. Forty, 26-week old laying pullets belonging to Shaver 579 strain was fed NLM for 12 weeks. Five dietary treatments, each of four replications, containing either 0, 5, 10, 15 or 20g NLM per kg were compared. The birds were reared in a pyramid-type laying cage. Blood and eggs were collected three times maintaining four weeks interval for the determination of cholesterol concentration respectively in serum and egg yolk. Eggs from birds laid after 6 weeks of feeding NLM were used for the determination of internal and external characteristics of eggs. Body weight gain, egg weight, total egg mass, FCR, survivability, and internal and external egg quality characteristics were studied. Use of NLM at 10 and 15 g/kg showed negative quadratic effect (P